(untitled) (Modern education and development, 2024)
ushbu maqolada xorazm viloyatida turizm sohasini rivojlantirishning istiqbollari ustuvor yo’nalishlari va tahlil natijalari hamda yo’nalish vazifalari xususidagi fikrlar ifoda etilgan. this article expresses the priorities of the prospects for the development of the tourism sector in the Khorezm region and the results of the analysis and points on the tasks of the direction.